2022
DOI: 10.2196/preprints.43256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dermatology Journals’ Editorial Boards Require Improved Gender Equity: JMIR Dermatology’s Future Directions (Preprint)

Abstract: UNSTRUCTURED Gender disparities exist across all facets of academic medicine including within dermatology journal editorial boards. Only 22% of these editorial boards are women even though 51% of full-time, faculty dermatologists are women [1, 2]. When inviting academics to our editorial board at JMIR Dermatology, we invited 50% women to represent the gender distribution of academic dermatologists; however, we have not sufficiently reached gender equity of accepted editorial board membe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Persistence may be necessary, as illustrated by the case of JMIR Dermatology which invited more women to join the editorial board. 69 The target composition of 50% female was not reached, but the journal recommitted to recruit more female Board members. 69 On a dermatology journal's website, adherence to the principle of gender equity should be mentioned, either as a 'stand alone' statement or as part of a broader pledge to 'diversity, equity and inclusion' (DEI).…”
Section: Striving For a Greater Representation Of Women Among Editors...mentioning
confidence: 99%
See 2 more Smart Citations
“…Persistence may be necessary, as illustrated by the case of JMIR Dermatology which invited more women to join the editorial board. 69 The target composition of 50% female was not reached, but the journal recommitted to recruit more female Board members. 69 On a dermatology journal's website, adherence to the principle of gender equity should be mentioned, either as a 'stand alone' statement or as part of a broader pledge to 'diversity, equity and inclusion' (DEI).…”
Section: Striving For a Greater Representation Of Women Among Editors...mentioning
confidence: 99%
“…69 The target composition of 50% female was not reached, but the journal recommitted to recruit more female Board members. 69 On a dermatology journal's website, adherence to the principle of gender equity should be mentioned, either as a 'stand alone' statement or as part of a broader pledge to 'diversity, equity and inclusion' (DEI). A recent survey of 60 dermatology journals found that only 5 (8%) referenced a commitment to DEI.…”
Section: Striving For a Greater Representation Of Women Among Editors...mentioning
confidence: 99%
See 1 more Smart Citation